nalisis Kuat Tarik Kayu Menggunakan PKKNI 1961 dan SNI 7973:2013 - Ahmad Hernadi; Noerman Adi Prasetya; Rahcmad Aidil (Borneo Engineering : Jurnal Teknik Sipil, 2017)
Use of wood construction in Indonesia is decrease significant than concrete and steel. While it is, government by National Standardization Corporation (BSN) had been published Indonesian National Standard about Wood Construction Design Spesification with code SNI 7973:2013. This code absolutly influential the old code which is PKKNI 1961. SNI 7973:2013 is regulate about Load esistance Factor Design (LRFD) and Allowable Stress Design (ASD), while PKKNI 1961 just use ASD method. In case SNI 7973:2013 have been use ASD, but it is different to PKKNI 1961. This research is would to find the different betwen SNI 7973:2013 and PKKNI 1961 to tension member with dimention 5/10, 6/12, 8/12 and 10/10. Result of research to tension member show that LRFD 100%, ASD 65,1% and PKKNI 111,4%.